2021
DOI: 10.1186/s12937-021-00701-9
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety is associated with appetitive traits in university students during the COVID-19 pandemic

Abstract: Background COVID-19 has impacted mental health globally, however, associations between anxiety and appetitive traits during the pandemic are unreported. This study evaluated anxiety symptom severity and associations with appetitive traits in students at a large public University in the U.S. during the pandemic. Methods Current undergraduate and graduate/professional students completed a cross-sectional survey in fall 2020. Demographic information, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 44 publications
0
24
0
3
Order By: Relevance
“…The COVID-19 crisis has presented unique challenges [ 3 ]; the pandemic has caused one of the worst crises in the world’s economy since the end of World War II [ 4 , 5 ]. COVID-19 has also changed people’s hygiene behaviors [ 6 , 7 ], and affected people’s food choice motive [ 8 , 9 , 10 , 11 , 12 , 13 ] and appetitive traits [ 14 , 15 ]. The pandemic, and the restrictive measures taken to control the pandemic, have often led to uncertainty in demand and supply disruptions, which have ultimately affected product prices and household food consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 crisis has presented unique challenges [ 3 ]; the pandemic has caused one of the worst crises in the world’s economy since the end of World War II [ 4 , 5 ]. COVID-19 has also changed people’s hygiene behaviors [ 6 , 7 ], and affected people’s food choice motive [ 8 , 9 , 10 , 11 , 12 , 13 ] and appetitive traits [ 14 , 15 ]. The pandemic, and the restrictive measures taken to control the pandemic, have often led to uncertainty in demand and supply disruptions, which have ultimately affected product prices and household food consumption.…”
Section: Introductionmentioning
confidence: 99%
“…University students have been affected by the lockdown periods with disruptions in teaching with the switch of online learning to continue teaching, leading to worries about adapting to new methods [4]. The implementation of public health measures (including gym closures and prohibited group sports) has caused a decrease in physical activity [5] and a modification of eating habits among university students [6,7]. A recent review of the literature concluded that quarantine measures and the pandemic COVID-19 could have negative psychological effects, including, stress, anxiety, and depression [8,9], higher among university students than non-students [10].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the COVID-19 pandemic, it must be noted that the present global situation may change food priorities [ 16 ]. Appetitive traits also appear to be influenced by the pandemic, as it was reported that in this period students experience moderate-to-severe anxiety symptoms due to increased hunger, emotional over-eating, and food and satiety responsiveness, as well as decreased enjoyment of food [ 17 ]. Thus, the associations of food preferences and appetitive traits may also be modified, and so they should be studied in the period of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%